Misdiagnosis of sphincter of Oddi disorder treated as familial Mediterranean fever for ten years: A case report. (February 2022) - Alkarrash, Mohamad Shadi; Shashaa, Mohammad Nour; Rhayim, Roaa; Aljarad, Ziad
Abstract: Introduction: Sphincter of Oddi dysfunction is a rare disease caused by sphincter of Oddi functional or mechanical abnormality. Misdiagnosis of familial Mediterranean fever is very high due to overlapping symptoms with many diseases. Our case is the first case report in the medical literature which describes the misdiagnosis of Sphincter of Oddi dysfunction as familial Mediterranean fever. Case presentation: A 46-year-old woman presented with recurrent episodes of abdominal pain and arthralgia. The patient had familial Mediterranean fever for ten years which was diagnosed clinically without performing genetic tests. Analysis of the mutation in the MEFV gene was performed and was negative. Thereby, the diagnosis of familial Mediterranean fever was eliminated and colchisine was discontinued. Afterward, laboratory and radiological tests were performed, and the diagnosis of sphincter of Oddi disfunction was confirmed. The patient underwent biliary sphincterotomy and take sulpiride daily. Discussion: The most common diseases were misdiagnosed with familial Mediterranean fever are appendicitis, acute rheumatic fever, gastrointestinal diseases and inflammatory arthritis. Endoscopic retrograde cholangiopancreatography with Manometry of the Sphincter of Oddi is the gold-standard test. Conclusion: Sphincter of Oddi dysfunction may interfere with many other disorders and should be considered as a differential diagnosis for any recurrent abdominal pain. Misdiagnosis of familial Mediterranean fever is common in endemic countries due to the reliance on clinical symptoms without analysis of the mutations in the MEFV genes particularly, before 1997. Highlights: SOD should be considered as a differential diagnosis for any recurrent abdominal pain. Misdiagnosis of familial Mediterranean fever is common in endemic countries. ERCP with Manometry of the Sphincter of Oddi is the gold-standard test.